Pengaruh Pengendalian Internal dan Sistem Informasi Akuntansi Terhadap Kinerja Pegawai pada Inspektorat Daerah Kota Gorontalo - Nur Sabriani Kaaba; Nilawaty Yusuf; Muliyani Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of internal control and accounting information systems on employee performance at the Gorontalo City Regional Inspectorate Office. The study uses a quantitative research method. The primary data source was obtained from a questionnaire distributed to State Civil Apparatus (ASN) at the Gorontalo City Regional Inspectorate. The data analysis technique in this study is descriptive quantitative analysis using the statistical t test, statistical f test and coefficient of determination test using IBM SPSS 27 for windows. The results of the study indicate that partially internal control and accounting information systems have a significant positive effect on Employee Performance at the Gorontalo City Regional Inspectorate. Then simultaneously internal control and accounting information systems have a significant effect on employee performance by 45.2% while the remaining 58.2% is explained by other variables not explained in this study.